Disparity in Judges' Decisions in Sexual Harassment Cases: A Juridical Analysis of Caning and Imprisonment Sentences in the Mahkamah Syar'iyah - Muharnina, Yusi; Kadafi, Muhammad; Saputra, Jummaidi (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
A judge in the Mahkamah Syar'iyah handed down different sentences in cases of sexual harassment. In Case Decision Number 6/JN/2019/MS.Mbo, the judge imposed a sentence of 30 lashes, while in Case Decision Number 7/JN/2017/MS.Mbo, a prison sentence of 24 months was given. This research aims to analyze the judge's considerations in imposing caning and imprisonment as well as the legal review of these punishments. The research method used is normative juridical research with the aim of uncovering the judge's considerations in delivering the verdicts. The legal materials used include primary, secondary, and tertiary legal materials. Data analysis was conducted qualitatively. The results of the research indicate that the judge’s consideration in imposing caning or imprisonment involved examining the charges filed by the public prosecutor, witness statements during the trial, the prosecutor's demands, the defendant's defense, the fulfillment or lack thereof of the elements of sexual harassment committed by the perpetrator, and factors that could either mitigate or aggravate the sentence based on the facts revealed in court. Legally, disparity in sexual harassment cases is permissible because the punishment threat is alternative in nature, allowing judges to choose caning, fines, or imprisonment, except in cases of sexual harassment with child victims. Following SEMA Number 2 of 2020, caning must be imposed on perpetrators in such cases. [Hakim Mahkamah Syar’iyah menjatuhkan hukuman yang berbeda pada kasus pelecehan seksual. Pada putusan Nomor Kasus 6/JN/2019/MS.Mbo hakim menjatuhkan hukuman dengan jumlah 30 kali cambuk. Sementara pada putusan Nomor 7/JN/2017/MS.Mbo dijatuhkan dengan hukuman 24 bulan. Penelitian bertujuan menganalisis pertimbangan hakim dalam menjatuhkan hukuman cambuk dan penjara serta tinjauan yuridis terhadap penjatuhan hukuman tersebut. Metode penelitian yang digunakan yaitu penelitian yuridis normatif dengan tujuan untuk mengungkapkan pertimbangan hakim dalam menjatuhkan putusan. Bahan hukum yang digunakan yaitu bahan hukum primer, bahan hukum sekunder dan bahan hukum tertier. Analisis data dilakukan secara kualitatif. Hasil penelitian menunjukkan bahwa pertimbangan hakim menjatuhkan ‘uqubat cambuk maupun penjara dengan mempertimbangkan dakwaan yang dituntut oleh penuntut umum, keterangan saksi di persidangan, tuntutan yang diajukan oleh penuntut umum, pembelaan yang disampaikan oleh terdakwa, terpenuhi atau tidaknya unsur pelecehan seksual yang dilakukan oleh pelaku dan hal-hal yang dapat meringankan maupun memberatkan sesuai dengan fakta-fakta yang terungkap di persidangan. Penelitian ini menyimpulkan bahwa disparitas putusan dalam kasus pelecehan seksual di Mahkamah Syar’iyah dapat dibenarkan secara hukum karena adanya fleksibilitas dalam aturan pemidanaan, meskipun setelah SEMA No. 2 Tahun 2020, pilihan hukuman menjadi lebih terbatas untuk kasus pelecehan seksual terhadap anak].